PROGRAMMING IN NATURAL LANGUAGE: PUBLICATIONS REVIEW - E. G. Luttsev (Informatika)
Paper addresses a number of scientific papers devoted to the issues of programming languages close to natural languages. Description of classical approaches to the design of natural programming languages and new approaches that have made the development of these languages practical is given. One of the high-level languages – CLIPS – is compared with natural programming languages. A monograph in Russian devoted to the natural language interfaces is reviewed.